2017
DOI: 10.3847/1538-4357/aa6973
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-wavelength Analysis of Dust and Gas in the SR 24S Transition Disk

Abstract: We present new Atacama Large Millimeter/sub-millimeter Array (ALMA) 1.3 mm continuum observations of the SR 24S transition disk with an angular resolution 0.18  ¢ (12 au radius). We perform a multi-wavelength investigation by combining new data with previous ALMA data at 0.45 mm. The visibilities and images of the continuum emission at the two wavelengths are well characterized by a ring-like emission. Visibility modeling finds that the ring-like emission is narrower at longer wavelengths, in good agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 69 publications
6
26
1
1
Order By: Relevance
“…Our model consists of a radially asymmetric Gaussian ring for the millimeter intensity (I(r))-that is, a Gaussian ring whose inner and outer widths (σ int and σ ext , respectively) can differ, such that where C is connected with the total flux of the disk as explained below. This profile was introduced in Pinilla et al (2017a) to fit the morphology of TDs and to mimic the effect of particle trapping in a radial pressure bump. From dust evolution models, it is expected that under the presence of a single pressure bump, the external width of the ring is larger than the internal because in the outer disk the particles take longer times to grow and drift toward the pressure maximum, creating a ring with an outer tail as discussed in Section 5.2.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model consists of a radially asymmetric Gaussian ring for the millimeter intensity (I(r))-that is, a Gaussian ring whose inner and outer widths (σ int and σ ext , respectively) can differ, such that where C is connected with the total flux of the disk as explained below. This profile was introduced in Pinilla et al (2017a) to fit the morphology of TDs and to mimic the effect of particle trapping in a radial pressure bump. From dust evolution models, it is expected that under the presence of a single pressure bump, the external width of the ring is larger than the internal because in the outer disk the particles take longer times to grow and drift toward the pressure maximum, creating a ring with an outer tail as discussed in Section 5.2.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…We used natural weighting for imaging (except for CIDA1 that uses uniform weighting; Pinilla et al 2018) to obtain as high sensitivity as possible. The final representative angular resolution is reported in Table 1.…”
Section: Observations and Sample Of Tdsmentioning
confidence: 99%
“…The cycle 2 ALMA 1.3 mm continuum images of SR24 with a resolution of 0. ′′ 18 are reported by Pinilla et al (2017). The 1.3 mm continuum images of SR24S disk are described by ring-like emission with a central cavity.…”
Section: Andrewsmentioning
confidence: 92%
“…The 1.3 mm continuum images of SR24S disk are described by ring-like emission with a central cavity. Fitting by Pinilla et al (2017) showed that the PA, inclination, and peak radius for the SR24S disk are 24.30 • , 46.31 • , and 0. ′′ 3, respectively.…”
Section: Andrewsmentioning
confidence: 99%
“…However, some objects display a lack of emission in the near and mid-infrared (NIR and MIR) compared to full disk systems' spectral energy distributions (SEDs; e.g., Calvet et al 2005). These objects have a disk with a large dust-depleted inner cavity that has been spatially resolved with sub-mm interferometry for individual objects (e.g., Andrews et al 2011;van der Marel et al 2013van der Marel et al , 2016Canovas et al 2015;Pinilla et al 2015Pinilla et al , 2017Dong et al 2017;Sheehan & Eisner 2017) and are called transition disks because they are believed to undergo the process of disk clearing. Between the full disk and the transitional disk stage, pretransitional objects show a depletion in the MIR but still have an excess of NIR emission, likely caused by the presence of an inner disk interior to the cavity, forming a gapped disk (e.g., Espaillat et al 2014;Kraus et al 2017).…”
Section: Introductionmentioning
confidence: 99%